INFLUENCE OF PHYSICAL EDUCATION TEACHERS ON THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGY IN THE LEVEL OF CREATIVITY AND COMMUNICATION SKILLS - Hossein Karimi Pashaki,; Vahid Bakhshalipour, (Sport Scientific And Practical Aspects, 2025)
The present study was conducted to link the use of information and communication technology with creativity and communication skills in physical education teachers. The statistical population of this study included all physical education teachers were randomly selected. Data collection was done by library and questionnaire. The tools used in the research were also valid. Data analysis was performed at two levels of descriptive and inferential statistics. In descriptive statistics, mean and standard deviation were used. In inferential statistics, first one-sample t-test and after confirming the parametric statistics and normal distribution of data using Kolmogorov-Smirnov test, Pearson correlation method, t Independently, used in SPSS software. The results showed that there is a significant relationship between the use of information and communication technology with the level of communication skills and creativity.